Scared or scarred: Could 'dissociogenic' lesions predispose to nonepileptic seizures after head trauma?. (May 2018) - Popkirov, Stoyan; Carson, Alan J.; Stone, Jon
Highlights: Traumatic brain injury (TBI) is common in psychogenic nonepileptic seizures (PNES). A possible connection is seen in maladaptive symptom modelling. Effects of mild brain injury can include disruption of functional connectivity. This disruption might temporarily fascilitate dissociation and PNES development. Mild TBI might be a cause of "dissociogenic" lesions in some patients. Abstract: A history of head injury is common in patients with psychogenic nonepileptic seizures (PNES). This association has so far been interpreted as either spurious or psychologically mediated. Biased recall and misattribution could foster illness beliefs about brain damage that promote symptom production. Furthermore, the emotional impact of head injury could induce long-term changes in stress responsivity. Lastly, maladaptive cognitive-behavioural processes involving symptom modelling and aversive conditioning, known to play a role in functional neurological disorders, could contribute to the development of PNES after head trauma. Lesional effects of head injury, on the other hand, remain unexplored in the context of PNES. However, even mild traumatic brain injury without structural MRI abnormalities on routine imaging can lead to disruptions of network connectivity that correlate with short-term cognitive impairments and psychiatric symptoms. Since alterations in global functional connectivity have been demonstrated in PNES patients using imaging and electroencephalography, we hypothesize that, in some patients, TBI and the associated disruption of long-range association fibres could contribute to the individual propensity for dissociative experiences in general and PNES in particular. This possibility is explored in the context of new cognitive-behavioural models of PNES pathogenesis, and the concept of a "dissociogenic" brain lesion is introduced.